PERLINDUNGAN HUKUM TERHADAP PERKAWINAN DI BAWAH UMUR DALAM PERSPEKTIF PERLINDUNGAN ANAK DI PENGADILAN NEGERI KABANJAHE - Selenc Gracia Pandia; Rayani Saragih; Maslon Hutabalian (Journal Recht (JR), 2025)
This study aims to determine the factors that cause underage child marriage and to determine the form of legal protection for underage marriage according to Law Number 35 of 2014 concerning child protection. The formulation of the problem in this study is the factors that cause underage child marriage and the form of legal protection for underage marriage according to Law Number 35 of 2014 concerning child protection. This research method is normative juridical research, namely through the study of regulations and various positive norms in legislation as regulations for human life. The data collection technique in this study was library research, namely data obtained from reading books, literature and legislation related to this writing, especially those related to legal protection against underage marriages seen in the child protection law and based on data from the Kabanjahe District Court.The results of the study indicate that internal factors (self-desire) where factors that influence young marriage can come from internal factors, namely factors originating from within the individual and external factors also cause children to marry underage, including economic factors, education, parents, mass media and the internet, biological, getting pregnant outside of marriage and customary factors. Meanwhile, legal protection for underage children who marry according to Law Number 35 of 2014 concerning child protection is seen based on preventive law and repressive law.